Discovery of 7-azaindole derivatives as potent Orai inhibitors showing efficacy in a preclinical model of asthma. Issue 6 (15th March 2015) - Esteve, Cristina; González, Jacob; Gual, Sílvia; Vidal, Laura; Alzina, Soledad; Sentellas, Sonia; Jover, Irene; Horrillo, Raquel; De Alba, Jorge; Miralpeix, Montserrat; Tarrasón, Gema; Vidal, Bernat
Graphical abstract: Abstract: Synthesis and SAR of a series of 7-azaindoles as Orai channel inhibitors showing good potency inhibiting IL-2 production in Jurkat cells is described. Compound14d displaying best pharmacokinetic properties was further characterized in a model of allergen induced asthma showing inhibition in the number of eosinophils in BALF. High lipophilicity remains as one of the main challenges for this class of compounds.